(3/10)x-3x+(4/5)=(3/5)

Simple and best practice solution for (3/10)x-3x+(4/5)=(3/5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3/10)x-3x+(4/5)=(3/5) equation:



(3/10)x-3x+(4/5)=(3/5)
We move all terms to the left:
(3/10)x-3x+(4/5)-((3/5))=0
Domain of the equation: 10)x!=0
x!=0/1
x!=0
x∈R
We add all the numbers together, and all the variables
(+3/10)x-3x+(+4/5)-((+3/5))=0
We add all the numbers together, and all the variables
-3x+(+3/10)x+(+4/5)-((+3/5))=0
We multiply parentheses
3x^2-3x+(+4/5)-((+3/5))=0
We get rid of parentheses
3x^2-3x+4/5-((+3/5))=0
We calculate fractions
3x^2-3x=0
a = 3; b = -3; c = 0;
Δ = b2-4ac
Δ = -32-4·3·0
Δ = 9
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{9}=3$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-3)-3}{2*3}=\frac{0}{6} =0 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-3)+3}{2*3}=\frac{6}{6} =1 $

See similar equations:

| 4x+8x-57=38-7 | | x-(15x-6)=107 | | 6x+3(3x+22)=216 | | 517=83-x | | 5c=c | | 517=83-c | | 85-4x=75-3.5x | | -8(7x+31)=-976 | | x+6/5-x-3/7=12/7 | | 7x+3(4x/)=109 | | 162-12x=-20x-246 | | -1x+1(x-1)=2 | | 60=2/3x+x | | 5(x-9)=35-3x | | (3x+33)(2x-3)=180 | | 3(w-5)-8w=5 | | 0.5(6x-4)=3x+2 | | 2(2x)+x=17.5 | | 1(x-1)=x+2 | | (3x–1=-10) | | -8x+83=-x-176 | | 11b+20=40 | | 12+4n=–4 | | -30-5x=123 | | (x-5)2=x+1 | | -12m+4m=18-3 | | c÷2=14 | | (x-5)^2=x+1 | | 8x-5=8(x-7) | | (x-5)²=x+1 | | 18y-6=3(6y-2) | | 1=-8y^2 |

Equations solver categories